Fecal Microbiota Transplantation Restores Immune Homeostasis in Patients with Ulcerative Colitis - Hammood, Mohammed I.; Makassees, Jawad N. K. (Journal of Science in Medicine and Life, 2025)
Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) marked by dysbiosis and immune system dysfunction. Standard treatment options, including immunosuppressive therapies, often provide insufficient long-term outcomes. Fecal microbiota transplantation (FMT) has emerged as a potential alternative, restoring gut microbial balance and immune homeostasis. Objective: This study aims to assess the effects of FMT on immune markers, microbial diversity, and clinical outcomes in UC patients. Methods: A total of 30 UC patients with moderate to severe disease underwent FMT via colonoscopy. Outcomes were measured by inflammatory cytokines (IL-6, TNF-α, IL-10), microbial diversity (Shannon index), and clinical remission rates at baseline, 4 weeks, and 12 weeks post-FMT. Results: FMT significantly reduced IL-6 and TNF-α levels while increasing IL-10. Microbial diversity improved, with a significant increase in the Shannon diversity index. Clinical remission was achieved in 73% of patients, and 61% showed mucosal healing by 12 weeks. Conclusion: FMT provides a promising therapeutic approach for UC by modulating immune responses and restoring microbial diversity, leading to clinical improvements in many patients.